PEMAKNAAN KEMBALI HADIS-HADIS KEUTAMAAN ORANG MISKIN DAN ORANG KAYA - Waluyo Lensa, Hendri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Poverty for most people the world is something that is very avoidable, and any government of a country formed by special departments in charge of poverty alleviation, including countries that are predominantly Muslim. Many factors that cause poverty that afflicts a social order, however it is precisely at the same time there are slogans conveyed the elements of public figures who have great influence in the course of the pattern of community life, from the teachers, the muballig they narrations brought traditions of the Prophet, which explains how great virtue to be poor. such as the hadith explains that most of the population of heaven is poor, poor people were entering heaven precede the rich, so that it does not realize that these traditions is misunderstood by most of the Muslim community and membutnya lazy and unwilling to work for a high work ethic. This paper describes some of the traditions that spread in society at a glance calls on Muslims to be weak and lazy do not have a high work ethic, while there are many hadiths of the Prophet which encourages his people to be a people strong, quality as well as the benefits for creatures other.